Community and Quality of Education: A Study on Perception and Motivation Towards Islamic Elementary School - Arfah, Muh.; Kaharuddin, Kaharuddin; K, Bulu (International Journal of Asian Education, 2024)
This research examines the community’s perception and motivation regarding the Darussalam Integrated Islamic Elementary School in Palopo City. The objectives are: 1) to explore the community's perception of the school, 2) to identify factors motivating families to choose the school, and 3) to evaluate the quality of education provided. Using a qualitative, descriptive field study approach, data was collected through observations, interviews, and documentation from parents and teachers. The analysis included data condensation, presentation, and conclusion drawing, with credibility ensured through extended observations, triangulation, and accuracy checks. The findings reveal that the community holds a highly positive perception of the school, valuing its ability to develop students' character and morals in line with Islamic teachings, alongside a strong focus on Qur’an literacy. The school’s comprehensive facilities and balanced integration of the Merdeka Curriculum and the Integrated Islamic School Network (JSIT) curriculum, combining general and Islamic studies, also contribute to this favorable view. Factors like parents’ educational background, economic status, and the school's location further influence their perceptions and decisions.